2019
DOI: 10.15171/japid.2018.008
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic comparison of density and height of posterior maxillary bone after open sinus lift surgery with and without PRF

Abstract: Background and aims. Expansion of maxillary sinus towards the alveolar crest due to tooth loss or horizontal‒vertical resorption of the alveolar bone decreases the available bone for the placement of dental implants in the posterior maxilla. The method suggested for placing implants with a standard length is the use of sinus lift surgery with autogenous bone graft or bone substitute materials. The aim of the present research, with split-mouth design, was radiographic comparison of the density and height of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A recent study reported contradictory data, showing no results in terms of bone gain after tooth extraction with L-PRF, but their histogical and radiological data were performed only 8 weeks after the surgical procedure [ 57 ]. Another study compared external sinus lift procedure with L-PRF and without any other material and found a 1.42 mm bone height gain for the group treated with L-PRF [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported contradictory data, showing no results in terms of bone gain after tooth extraction with L-PRF, but their histogical and radiological data were performed only 8 weeks after the surgical procedure [ 57 ]. Another study compared external sinus lift procedure with L-PRF and without any other material and found a 1.42 mm bone height gain for the group treated with L-PRF [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Implants were placed in one session. This study ( Table 3 ) stated that PRF may improve both the quantity and quality of bone resorption [ 27 ].…”
Section: Discussionmentioning
confidence: 99%